Evaluation of the effects of electric vehicle battery cells layout and conductive sheet fins thickness to battery cooling using transportation micro-simulation modeling and finite element steady-state thermal analysis - Rito, Joshua Ezekiel Dimaunahan (Animo Repository, 2022)
Simultaneous to the rapid increase of electric vehicles in terms of popularity and quantity are the constant developments and advancements in the technology. One of the key areas of concern related to the development of electric vehicle is the thermal management on the battery system that, generally, is composed of lithium-ion battery cells. It is a known fact that lithium-ion batteries generate heat during operation, and the performance, lifespan and safety of the batteries are at risk if the heat generated is not properly managed. Thus, several battery thermal management systems are continuously being studied to prevent the risks from materializing and to further improve the current technologies. Specifically, a number of research is being conducted to improve the performance and increase the efficiency of the battery thermal management systems. In this paper, the author examines design factors that can affect the performance of a battery cooling system for an electric vehicle project in the Philippines. Small but deemed significant design factors such as conductive sheet fins thickness and battery cell layouts are investigated using transportation micro-simulation modeling and finite element steady-state thermal analysis. To systematically evaluate the design factors and their effects to battery cooling, an experimental design is utilized particularly the random complete block design (RCBD). The study also discusses the relevant input data and assumptions used as well as the key findings in the course of the micro-simulation transport model and the finite element thermal analyses. Results showed that the effects of battery cells layout and conductive sheet fins thickness have both significant impacts on the temperature of battery cells. Ultimately, the study recommends the use of battery modules with 4 x 7 cell layout and 1 mm conductive sheet fins in relation to technical and practical perspective.